Topological field labeler for German - Do, Bich-Ngoc; Rehbein, Ines (Universität, 2023)
This resource contains the code of the topological labeler used in the paper: Do and Rehbein (2020). "Parsers Know Best: German PP Attachment Revisited". For this tool, labeling topological field is formulated as a sequence labeling task. We also include in this resource two pre-trained models on the TüBa-D/Z dataset with German SPMRL styled POS tags that are used in the paper.